PENGUJIAN TECHNOLOGY ACCEPTANCE MODEL PADA MOBILE BANKING SEBAGAI DETERMINAN PERFORMA UMKM DI KOTA MAKASSAR - Syarief Dienan Yahya; Harry Yulianto (Jurnal Bisnis dan Kewirausahaan, 2019)
Technology adoption plays an important role in competing and creating opportunities in business nowadays. Mobile Banking has changed the way the banking industry and business interact. Mobile Banking is an alternative business strategy for businesses to survive in an increasingly competitive business in today's digital era. This study will focus on adopting Mobile Banking technology and its role to improve the performance of Micro, Small and Medium Enterprises (MSMEs) by adapting the Technology Acceptance Model concept using several indicators from various previous studies which consist of Perceived Ease of Use, Perceived Usefulness, Social Norms, Perceived Risk, Relative Advantages, Personal Innovativeness and Cost as indicators. The study involved 278 Micro, Small and Medium Enterprises (MSMEs) in Makassar City by using a self-administered questionnaire, which was determined using the Purposive Sampling method. The result shows that simultaneously all indicators of the construct of Technology Acceptance Model had a positive and significant influence on the performance of Micro, Small and Medium Enterprises (MSMEs) in Makassar City. Furthermore, partially each indicator shows a positive and significant influence and personal innovativeness is the most dominant indicator in influencing Micro, Small and Medium Enterprises (MSMEs) performance. The findings of this study are expected to enrich the study related to the topic of Technology Acceptance Model in Mobile Banking and its relationship to improving the performance of Micro, Small and Medium Enterprises (MSMEs).